(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
This article analyzes ways to reduce the hidden economy through tax control. In this, the specific features of the reforms carried out in the tax authorities were studied. It has also been studied that digitalization of tax administration is one of the main tools to curb the underground economy. In this regard, the opinions and comments of foreign and local scientists were studied. Also, proposals and recommendations have been formulated to improve ways to reduce the share of the hidden economy in our country